Dijital pazarlama yaklaşımı açısından webcare kalitesinin olumlu ağızdan ağıza pazarlama niyeti üzerindeki rolü ve bir araştırma - Kuşat, Gülşah (My University, 2022)
DİJİTAL PAZARLAMA YAKLAŞIMI AÇISINDAN WEBCARE KALİTESİNİN OLUMLU AĞIZDAN AĞIZA PAZARLAMA NİYETİ ÜZERİNDEKİ ROLÜ VE BİR ARAŞTIRMA

Social media makes it possible for consumers to easily share their shopping experiences with other consumers. These shares about brands are mostly about negative experiences rather than positive ones. Sharing these negative experiences on the internet directly affects the purchasing decisions of other consumers; therefore, they have become a major concern for brands. In order to mitigate the effects of NWOM shared on the internet, brands try to control the process by replying to these comments. This process, namely the management of negative comments online, is known as webcare in the world literature. Webcare focuses on the purpose of restoring or increasing customer satisfaction and limiting the potential harm that negative eWOM can have on other consumers. The desired outcome with this practice is that complaining customers stop spreading negative eWOM and start spreading positive WOM about the company. This study focused on investigating the effect of 9 elements of webcare quality on positive word of mouth intention. The research was conducted with 531 participants who shop online once a year or more frequently. Data were collected by electronic survey method. As a result of the research; It has been determined that ownership, coherence and personalization, which are the elements of webcare quality, have a positive effect on positive word of mouth marketing intention.
Keywords: Business; digital marketing; dijital pazarlama; Electronic commerce; Elektronik ticaret; İşletme; mouth marketing intent; olumlu ağızdan ağıza pazarlama niyeti; online comment management; online response; online yanıt; online yorum yönetimi; positive word of; Webcare; webcare kalitesi; webcare quality